Comparison of entecavir and adefovir for the treatment of chronic hepatitis B - Zhao,Si-Hai (2012)
The results of several new clinical trials that compared the effectiveness of entecavir (ETV) treatment with that of adefovir (ADV) treatment in patients with chronic hepatitis B (CHB) were published in recent years. However, the numbers of patients included in these clinical trials were too small to draw a clear conclusion as to whether ETV is more effective than ADV. Therefore, a new meta-analysis was needed to compare ETV with ADV for the treatment of CHB. A search of the Cochrane Central Register of Controlled Trials (CCTR), MEDLINE, the Science Citation Index, Embase, the China National Knowledge Infrastructure (CNKI), and the Wanfang Database for relevant studies published between 1966 and 2010 was performed. Trials comparing the use of ETV and ADV for the treatment of CHB were assessed. Of the 2,358 studies screened, 13 randomized controlled clinical trials comprising 1,230 patients (ETV therapy, 621; ADV therapy, 609) were analyzed. The serum hepatitis B virus (HBV) DNA clearance rate obtained in patients treated with ETV was significantly higher than that in patients treated with ADV at the 24th and 48th weeks of treatment (24 weeks: 59.6% vs. 31.8%, relative risk [RR], 1.82, 95% CI: 1.49-2.23; 48 weeks: 78.3% vs. 50.4%, RR, 1.61, 95% CI: 1.32-1.96). The serum HBeAg clearance rate, the HBeAg seroconversion rate, and the ALT normalization rate obtained for patients treated with ETV were also higher than the corresponding values for patients treated with ADV at the 48th week of treatment. The safety profiles were similar between patients treated with ETV and those treated with ADV. The evidence reviewed in this meta-analysis suggests that patients with hepatitis B have a greater likelihood of achieving a viral response and a biomedical response when treated with ETV than when treated with ADV.